Features of hardiness depending on dominant coping strategies of personality - Danyliuk, Ivan; Predko, Viktoria; Bondar, Maksym (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
B a c k g r o u n d . Hardiness is an important psychological characteristic of a personality that helps to overcome difficulties and solve stressful life situations. Despite certain differences between the concepts of hardiness and coping strategies, studies (Olefir, 2011; Predko & Bondar, 2022; Soderstrom, Dolbier, Leiferman, & Steinhardt, 2000) demonstrate the relationship between coping strategies and personality hardiness. On the one hand, hardiness is determined by a person's ability to engage in constructive coping strategies aimed at overcoming life difficulties, and on the other hand, it is its effective expression.P u r p o s e : to build a prognostic model that will allow to determine the level of hardiness depending on the chosen coping strategies.M e t h o d s . "Test of hardiness", adaptation of D. A. Leontiev and O. I. Rasskazova; measure "Coping Strategy Indicator" by J. Amirkhan, adapted by V. M. Yaltonsky; "Ways of Coping Questionnaire" by R. Lazarus; questionnaire "Proactive Coping Inventory" by L. Aspinwall, E. Greenglass, R. Schwarzer, S. Taubert, adapted by O. Starchenkov. Regression analysis was performed to create a prognostic model.R e s u l t s . A prognostic model was developed that allows for identifying the level of hardiness depending on the dominant coping strategies.Using regression analysis, it was proved that three predictors have the greatest influence, namely problem avoidance, proactive coping, and planful problem-solving.C o n c l u s i o n . It was found that the choice of coping strategies determines the overall level of a person's hardiness and his or her ability to effectively withstand any situation. The study has shown that the proactivity of an individual, emotional self-regulation, and the ability to calculate the time perspective are the main factors in the successful overcoming of difficulties. At the same time, attempts to avoid negative experiences and denial of the problem impede the manifestation of hardiness.. However, further research is needed to develop the model in greater detail.
Keywords: hardiness; personality; coping strategies; problem avoidance; proactive coping; planful problem-solving